Reduced levels of serum vitamin B12 in symptomatic cases of oral lichen planus: A cross-sectional study - Shantala R. Naik; Prashant Gupta; Tanya Khaitan; Anjani Kumar Shukla (Elsevier, 2020)
Objectives: Oral Lichen Planus (OLP) is an immune mediated disease and causes oro-mucosal burning sensation that reduces food intake and hence resulting in nutritional deficiency. The present study was done to evaluate the serum levels of vitamin B12 in patients with symptomatic OLP and establish an association between reduced B12 levels and OLP. Materials and method: Serum vitamin B12 was assessed in 60 symptomatic cases of oral lichen planus and 60 healthy age and gender matched controls. Results: Serum vitamin B12 was significantly reduced (p value < 0) in patients with oral lichen planus when compared to healthy individuals. 43.33% of cases (26 out of 60) had B12 levels less than 187 pg/ml. Conclusion: Oral lichen planus causes serum vitamin B12 deficiency. Vitamin B12 is linked with normal functioning of immune and neuropsychologic system which has a role to play in etiopathogenesis and malignant transformation of oral lichen planus.